2017
DOI: 10.1200/jco.2017.35.4_suppl.673
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of atezolizumab (atezo) and bevacizumab (bev) in a phase Ib study of microsatellite instability (MSI)-high metastatic colorectal cancer (mCRC).

Abstract: 673 Background: Blockade of the PD-L1/PD-1 axis is a proven immunologic approach for treatment of many cancers; however, not all pts respond to monotherapy. Bev, an anti–VEGF-A antibody, has demonstrated clinical efficacy in mCRC and enhanced T-cell infiltration in tumors in preclinical studies. Thus, we postulated that combining atezo (anti-PD-L1) with bev would augment anti-tumor immune responses, resulting in improved and more durable clinical benefit. We report results from the first study of an anti-PD-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 0 publications
1
39
0
2
Order By: Relevance
“…Воздействие на ангиогенез, в частности моноклональными антителами к фактору роста эндотелия сосудов (vascular endothelial growth factor, VEGF), может проявлять синергизм с анти-PD-1-ингибиторами в отношении противоопухолевого эффекта [44], это было показано и на мышиных моделях РТК с высоким уровнем VEGF-A, но такая комбинация приводила к уменьшению в опухоли доли CD8 + -Т-лимфоцитов, экспрессирующих иммунные чекпоинты [49]. Однако значимого усиления эффективности анти-PD-L1-антител в клиническом исследовании получено не было: комбинация атезолизумаба с бевацизумабом у 10 больных MSI-положительным РТК привела к подтвержденному объективному эффекту у 30 % пациентов, к стабилизации -у 60 % [50].…”
Section: ингибиторы иммунных чекпоинтовunclassified
“…Воздействие на ангиогенез, в частности моноклональными антителами к фактору роста эндотелия сосудов (vascular endothelial growth factor, VEGF), может проявлять синергизм с анти-PD-1-ингибиторами в отношении противоопухолевого эффекта [44], это было показано и на мышиных моделях РТК с высоким уровнем VEGF-A, но такая комбинация приводила к уменьшению в опухоли доли CD8 + -Т-лимфоцитов, экспрессирующих иммунные чекпоинты [49]. Однако значимого усиления эффективности анти-PD-L1-антител в клиническом исследовании получено не было: комбинация атезолизумаба с бевацизумабом у 10 больных MSI-положительным РТК привела к подтвержденному объективному эффекту у 30 % пациентов, к стабилизации -у 60 % [50].…”
Section: ингибиторы иммунных чекпоинтовunclassified
“…A combination of atezolizumab with bevacizumab was explored in a separate cohort of the above study and preliminary outcomes were reported for a subset of patients with metastatic colorectal cancer with microsatellite instability (MSI-high). 40 Patients received atezolizumab 1200 mg with bevacizumab 15 mg/kg every 3 weeks. In this subset, the RR was 30% and 40% of patients experienced a treatment related AE though only one led to discontinuation of atezolizumab.…”
Section: Phase Ichemotherapy/biologic Combinationsmentioning
confidence: 99%
“…In a murine CRC model, a synergistic antitumor effect was observed with simultaneous VEGFR-2 and programmed cell death 1-ligand 1 (PD-L1) blockade, with increased CD8-positive and CD4-positive T cell infiltration into tumor tissue [41]. In the clinical setting, phase I/II trials are ongoing, assessing combinational therapies with anti-CTLA-4 (cytotoxic T lymphocyte-associated antigen 4) and anti-PD-(L)1 antibodies and bevacizumab in MSI-CRC and in unselected mCRC [42,43]. First results were promising, and the initiation of larger phase III studies is ongoing.…”
Section: Combination With Immunotherapymentioning
confidence: 99%